Overcoming the Divide Between Evidence-Based Education and Its Critics: An Alternative Conceptualization of the Relationship Between Academic Knowledge and Educational Practice - Clarà, Marc (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2026)
This paper addresses the current divide in the field of education between proponents and critics of evidence-based education. It examines the nature of this divide and argues that it is caused by a particular way of conceptualizing the relationship between academic knowledge and practice, called technical rationality, that is shared by both sides. The paper argues that technical rationality is fallacious and highlights an alternative approach grounded in the centrality of people’s understanding of situations of practice. It further argues that this alternative conceptualization of the relationship between knowledge and practice makes it possible to overcome the divide and foster advancement toward a science-based education.